Clinical Implementation of Cardiac Resynchronization Therapy—Regional Disparities across Selected ESC Member Countries. Issue 1 (26th December 2014) - Hatala, R.; Lunati, M.; Calvi, V.; Favale, S.; Goncalvesová, E.; Haim, M.; Jovanovic, V.; Kaczmarek, K.; Kautzner, J.; Merkely, B.; Pokushalov, E.; Revishvili, A.; et al.
<x xml:space="preserve">Abstract</x> Background The present analysis aimed to estimate the penetration of cardiac resynchronization therapy (CRT) on the basis of the prevalence and incidence of eligible patients in selected European countries and in Israel. Methods and Results The following countries were considered: Italy, Slovakia, Greece, Israel, Slovenia, Serbia, the Czech Republic, Poland, Romania, Hungary, Ukraine, and the Russian Federation. CRT penetration was defined as the number of patients treated with CRT (CRT patients) divided by the prevalence of patients eligible for CRT. The number of CRT patients was estimated as the sum of CRT implantations in the last 5 years, the European Heart Rhythm Association (EHRA) White Book being used as the source. The prevalence of CRT indications was derived from the literature by applying three epidemiologic models, a synthesis of which indicates that 10% of heart failure (HF) patients are candidates for CRT. HF prevalence was considered to range from 1% to 2% of the general population, resulting in an estimated range of prevalence of CRT indication between 1000 and 2000 patients per million inhabitants. Similarly, the annual incidence of CRT indication, representing the potential target population once CRT has fully penetrated, was estimated as between 100 and 200 individuals per million. The results showed the best CRT penetration in Italy (47–93%), while in some countries it was less than 5% (Romania, Russian Federation, and Ukraine). Conclusion CRT penetration differs markedly among the countries analyzed. The main barriers are the lack of reimbursement for the procedure and insufficient awareness of guidelines by the referring physicians.